Analisis Minat Berwirausaha Pada Mahasiswa Fakultas Ekonomi dan Bisnis Islam IAIN Parepare - Hasan, Nur Asima (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2023)
Entrepreneurship has become an important concern in increasing the country's economic growth, in conditions of the number of jobs that are unable to accommodate the large number of workforce which results in large numbers of unemployed, not many students themselves are pursuing the world of entrepreneurship due to various factors. The purpose of this study was to analyze the interest in entrepreneurship in students of the Islamic Faculty of Economics and Business IAIN Parepare to find out to what extent students of the Islamic Faculty of Economics and Business have an entrepreneurial interest considering the background of the faculty in lectures so far. The results showed that students' interest in entrepreneurship existed, but there was a lack of knowledge and understanding and motivation from the lecture environment, where motivation had quite an effect on interest in entrepreneurship.